Pre-existing turbulence and its influence on particle acceleration at astrophysical shocks - Ha, Ji-Hoon (Astrophysics and space science, 2025)
Understanding the physics of particle acceleration at shocks is a long-standing problem in space science and astrophysics. Because particles are energized across the shock upstream and downstream through Diffusive Shock Acceleration (DSA), the characteristics of upstream and downstream plasma waves involved in wave-particle interactions have been extensively examined. While many studies have focused on self-excited plasma instabilities due to shock-reflected and accelerated particles, the roles of pre-existing turbulence in astrophysical environments could be substantial for wave-particle interactions near the shock. This work specifically investigates the effects of pre-existing turbulence in the shock upstream on DSA efficiency. The normalization and slope of turbulent spectra are used as parameters to determine the characteristics of pre-existing turbulence. Since pre-existing turbulence can confine particles upstream and regulate their efficient acceleration through DSA across the shock, the DSA efficiency decreases as the strength of turbulence increases. Furthermore, the effects of pre-existing turbulence become less significant in plasma systems with higher plasma beta, as diffusion mediated by both self-excited waves and pre-existing turbulence becomes less efficient as plasma beta increases. The modeling presented in this work could be generally applicable to shocks propagating through turbulent regions.